Implementasi Kesenian Gong Renteng Terhadap Kebersamaan Masyarakat antar Umat Beragama di Kelurahan Sukamulya, Kuningan - Hani, Nur Izzati; Sintiya, Alvina Martha; Hidayah, Silviani; Purwadi, Reza; Aziz, Rohmanur; Saputra, M Dirga (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Indonesia is known for its rich diversity, including in the arts. In Kelurahan Sukamulya, Kuningan, Cigugur, there is a unique art form called Gong Renteng. This study investigates how the Gong Renteng art form is implemented in a community with diverse religious backgrounds. The research method uses a qualitative approach. Data collection techniques include observation, interviews, and document studies. Interviews were conducted to obtain information about the Gong Renteng art in Kelurahan Sukamulya, while document studies were used to obtain related documents such as photos or past data. The results of the study show that the Gong Renteng art form is not a problem for the community in Kelurahan Sukamulya. In fact, Gong Renteng itself serves as a medium to unite the community with diverse religious backgrounds and trains them to practice moderation and tolerance.